Considering the nutritional benefits and health implications of red meat in the era of meatless initiatives - Kavanaugh, Melissa; Rodgers, Diana; Rodriguez, Nancy; Leroy, Frédéric (Frontiers in Nutrition, 2025)
Driven by perceived health and environmental benefits, initiatives to remove red meat from recommended eating patterns are increasingly being implemented in United States institutions, including schools and hospitals. While these efforts aim to address important issues, they may inadvertently lead to unintended consequences, particularly regarding essential nutrient intake for certain populations. This perspective considers the nutritional value of red meat, examines its potential health benefits, and highlights nutritional risks when intake is reduced or eliminated. Red meat is a nutrient-dense food that provides highly bioavailable protein and several essential micronutrients often lacking in the diet, including iron, zinc, and vitamin B12. These nutrients can be limited or absent in many plant-source foods as well as in some animal-source foods. Red meat’s micronutrient profile is especially valuable for young children and women of reproductive age, including pregnant women. In addition, the protein density of red meat is beneficial for individuals managing obesity and older adults at risk of sarcopenia. Many epidemiological studies suggest potential associations between excessive red meat consumption and increased risk of certain chronic diseases, but this evidence does not conclusively implicate red meat in the development or progression of chronic disease. The nutritional and health implications of reducing red meat consumption must be balanced against the low certainty of evidence used to discourage red meat intake when making dietary recommendations.